2017
DOI: 10.3390/s17081798
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of HbA1c Biosensors

Abstract: Glycated hemoglobin (HbA1c) is formed via non-enzymatic glycosylation reactions at the α–amino group of βVal1 residues in the tetrameric Hb, and it can reflect the ambient glycemic level over the past two to three months. A variety of HbA1c detection methods, including chromatography, immunoassay, enzymatic measurement, electrochemical sensor and capillary electrophoresis have been developed and used in research laboratories and in clinics as well. In this review, we summarize the current status of HbA1c biose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 77 publications
(80 reference statements)
0
12
0
1
Order By: Relevance
“…The HbA1c-lowering effect of dapagliflozin was greater among patients with stable concentrations relative to all 72 patients (Table 2). HbA1c is formed via non-enzymatic glycosylation reactions, and it reflects the ambient glucose level over the past 2-3 months [19,20]. Therefore, maintaining the glucose level seems to be important in lowering HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…The HbA1c-lowering effect of dapagliflozin was greater among patients with stable concentrations relative to all 72 patients (Table 2). HbA1c is formed via non-enzymatic glycosylation reactions, and it reflects the ambient glucose level over the past 2-3 months [19,20]. Therefore, maintaining the glucose level seems to be important in lowering HbA1c levels.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that increasing Treg cells reduces the infiltration of macrophages in adipose tissue, which is important for alleviating IR. 172 In addition, the damage to the diversity and amount of SCFAs-producing bacteria in the gut increases the glycated hemoglobin (HbA1c) level in T2DM patients, 173 a kind of protein that represents the average plasma glucose levels over the past 2 to 3 months, 174 suggesting that the poor glycemic control.…”
Section: Gut Microbiota Dysbiosis and The Risk Factors For Ischemic S...mentioning
confidence: 99%
“…Development in HbA1c biosensors is also ongoing, and it is expected that in the future patients will have access to personal point-of-care HbA1c measurements that can be streamed to smartphones [37].…”
Section: Diabetes Managementmentioning
confidence: 99%